2020
DOI: 10.1021/jacs.0c03972
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structure of a Cyclic-PIP–DNA Complex in the Reverse-Binding Orientation

Abstract: Elucidation of the details of the associating mode is one of the major concerns for the precise design of DNA-binding molecules that are used for gene regulation. Pyrrole-imidazole polyamide (PIP) is a well-established synthetic DNA-binding molecule that has sequence-specificity for duplex DNA. By the design of the sequence of pyrrole, imidazole, and other synthetic units, PIP is bound to the target DNA sequence selectively. Here, we report the X-ray crystal structure of newly synthesized chiral cyclic PIP (cP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The binding of hairpin Py-Im 1 leads to minor groove widening as well as major groove compression of the DNA duplex in a similar manner as cyclic Py-Im molecules ( SI Appendix , Fig. S1 C ) ( 33 , 34 , 42 , 43 ). This high-resolution structure hairpin Py-Im–dsDNA complex was used as a starting model for building the downstream Py-Im–dsDNA region of the Pol II EC–Py-Im complex and paved the way for our structural studies of Py-Im–induced Pol II–arrested complexes.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The binding of hairpin Py-Im 1 leads to minor groove widening as well as major groove compression of the DNA duplex in a similar manner as cyclic Py-Im molecules ( SI Appendix , Fig. S1 C ) ( 33 , 34 , 42 , 43 ). This high-resolution structure hairpin Py-Im–dsDNA complex was used as a starting model for building the downstream Py-Im–dsDNA region of the Pol II EC–Py-Im complex and paved the way for our structural studies of Py-Im–induced Pol II–arrested complexes.…”
Section: Resultsmentioning
confidence: 87%
“…Our structure shows the conserved base recognition pattern between Py-Im and DNA base pairs: Im/Py recognizes G/C and Py/Py recognizes A/T or T/A ( SI Appendix , Fig. S1 B ) ( 33 , 34 , 42 , 43 ). The binding of hairpin Py-Im 1 leads to minor groove widening as well as major groove compression of the DNA duplex in a similar manner as cyclic Py-Im molecules ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Abe et al. [ 31 ] have confirmed the reverse orientation binding preference of chiral cPIP to the DNA minor groove through the X‐ray crystal structure of cPIP complexed with DNA at 1.5 Å resolution (Figure 2D,E). From the crystal structure, the positions of the hydrogen bonds between the bases and the cPIP moieties were similar for both forward‐ and reverse‐binding orientations.…”
Section: Binding Orientation Of Pips – Forward or Reverse?mentioning
confidence: 80%
“…Hence, the amino groups at the 𝛾-turn units could be positioned into PIPs to shift the orientation preference exclusively toward the reverse binding when it was difficult to target by the forward binding modes such as 5′-XXXG-3′ or 5′-GXG-3′. [28][29][30] Abe et al [31] have confirmed the reverse orientation binding preference of chiral cPIP to the DNA minor groove through the X-ray crystal structure of cPIP complexed with DNA at 1.5 Å resolution (Figure 2D,E). From the crystal structure, the positions of the hydrogen bonds between the bases and the cPIP moieties were similar for both forward-and reverse-binding orientations.…”
Section: Binding Orientation Of Pips -Forward or Reverse?mentioning
confidence: 99%
“…In some cases, however, they prefer binding in the reverse orientation . And several studies indicated that structural differences affect the orientation preferences of PIPs. In order to find PIP-based RUNX inhibitors with high efficiency and low off-target effect, we prepared not only conjugate 1 but also three analogs of conjugate 1 (conjugates 2 – 4 ; Figures and S2–S5). Conjugate 2 recognizes RUNX-binding sequences in a forward binding orientation similar to that of conjugate 1 , but the positions of its γ-turn and Chb are point-symmetric with conjugate 1 .…”
Section: Resultsmentioning
confidence: 99%